Determinants of job satisfaction among generation Y employees in banking sector - Bavithira, Vijakumaran (2020)
The main objective of the bank is to promote monetary and financial stability for the reasonable development of the Malaysian economy. Towards this end, the bank assumes a vital job in the improvement of a dynamic and comprehensive money related area which involves safeguarding the center establishments of monetary dependability consistently, guaranteeing powerful and effective budgetary intermediation, and contributing towards financial development and advancement. This research examines the factor that affect the job satisfaction of Gen Y in banking sector and the relationship established between job satisfaction and the motivation factors such as supervisor, salary, reward and work flexibility. Statistics was collected from 320 respondents which are selected randomly by using simple random sampling technique from the various department of commercial bank in Klang Valley. The data then was analysed using SPSS Version 22.0. The factors that affect job satisfaction among the employee will increase the turnover rate.